Monitoring of Epstein-Barr Virus DNA Load in Peripheral Blood by Quantitative Competitive PCR - Stevens, Servi J. C. (American Society for Microbiology, 1999)
A competitive quantitative PCR (Q-PCR) assay combined with simple silica-based DNA extraction was developed for monitoring of Epstein-Barr virus (EBV) DNA load in unfractionated peripheral blood. The Q-PCR is based on competitive coamplification of a highly conserved 213-bp region of the EBNA-1 open reading frame with an internal standard (IS), added in a known concentration. The IS has the same amplicon length and base composition as the wild-type (WT) EBNA-1 amplicon but differs in 23 internally randomized bases. Competitive coamplification yields two PCR products that are quantified by enzyme immunoassay or by electrochemiluminescence detection, with probes specific for the 23 differing internal nucleotides. The Q-PCR has a sensitivity of 10 copies of either WT or IS plasmid DNA. The Q-PCR was validated by quantification of known amounts of plasmid containing the WT EBNA-1 target. Furthermore, we determined EBV genome copy numbers in different cell lines. For EBV quantification in clinical samples, DNA was isolated from lysed whole blood by silica-affinity purification. Forty-six percent of healthy donor peripheral blood samples were positive by Q-PCR. In most of these samples, viral load was less than 2,000 EBV copies/ml of blood. In peripheral blood samples from two AIDS-related non-Hodgkin’s lymphoma patients, elevated EBV loads (up to 120,000 copies/ml) were observed, which decreased upon therapy. In Burkitt’s lymphoma patients, up to 4,592,000 EBV genome copies/ml of blood were detected. In conclusion, the EBNA-1-based Q-PCR assay provides a reproducible, accurate, and easy method for studying the relationship between EBV load and clinical parameters.